2015
DOI: 10.4103/2278-330x.173174
|View full text |Cite
|
Sign up to set email alerts
|

Occupation, smoking, opium, and bladder cancer: A case–control study

Abstract: Purpose:The aim of this study was to investigate occupational risk factors associated with bladder cancer.Materials and Methods:In this case–control study, control group included patients who referred to a specialized clinic in the same city and hospitals where patients had been registered. Data were entered into SPSS software. Odds ratios (OR) were calculated for occupational variables and other characteristics. Then, using logistic regression, the association between cancer and drugs was studied while smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…The remained 813 papers were screened based on their titles and abstracts and 785 irrelevant articles were removed. During a full text review of 28 papers [ 7 , 9 – 13 , 21 – 42 ], 11 papers were excluded [ 12 13 , 34 – 42 ]. Finally, 17 studies [ 7 , 9 – 11 , 21 – 33 ] were entered into the quality assessment and meta-analysis ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remained 813 papers were screened based on their titles and abstracts and 785 irrelevant articles were removed. During a full text review of 28 papers [ 7 , 9 – 13 , 21 – 42 ], 11 papers were excluded [ 12 13 , 34 – 42 ]. Finally, 17 studies [ 7 , 9 – 11 , 21 – 33 ] were entered into the quality assessment and meta-analysis ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…During a full text review of 28 papers [ 7 , 9 – 13 , 21 – 42 ], 11 papers were excluded [ 12 13 , 34 – 42 ]. Finally, 17 studies [ 7 , 9 – 11 , 21 – 33 ] were entered into the quality assessment and meta-analysis ( Fig 1 ). The kappa statistic was 0.77 indicating substantial agreement between the researchers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An elevated risk of bladder cancer was observed among a priori high-risk jobs including metal manufacturing, textile, driving, agriculture and livestock, and construction. Ghadimi et al (2015) [13] reported on a hospital-based case-control study on urinary bladder cancer in relation to occupation, smoking, and opium consumption, conducted in the Kurdistan Province. By the occupation classification ISCO-08, univariable analysis showed an elevated risk of bladder cancer in workers in metal manufacturing.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39] Second, GCS was the first study to prospectively follow a large number of opium users for more than a decade with a negligible loss to followup, allowing robust investigation of the risk of different cancer outcomes among these individuals. 12 Altogether, since 2003, at least 25 independent case-control, 24,[28][29][30][31][32][33][34][35][36][37][38][40][41][42][43][44][45][46][47][48][49][50][51][52] and 2 cohort studies 12,39 have been conducted on this subject and nearly all have shown increased risk of cancers of different sites among opium users . Reviewing the results of all studies conducted over the past 50 years, the IARC Working Group found "sufficient evidence" for the carcinogenicity of opium consumption in relation to cancers of the larynx, lung, and bladder, and "limited evidence" for the carcinogenicity of opium for cancers of the esophagus, stomach, pharynx, and pancreas.…”
Section: Fifty Years Of Investigations On Opium Use and Cancer Riskmentioning
confidence: 99%